Evidence against a role for the parkinsonism-associated protein DJ-1 in methylglyoxal detoxification - Pfaff, Daniel; Fleming, Thomas; Nawroth, Peter Paul; Teleman, Aurelio A. (The journal of biological chemistry, 2017)
Methylglyoxal (MG) is a reactive metabolite that forms adducts on cysteine, lysine and arginine residues of proteins, thereby affecting their function. Methylglyoxal is detoxified by the Glyoxalase system, consisting of two enzymes, Glo1 and Glo2, that act sequentially to convert MG into d-lactate. Recently, the Parkinsonism-associated protein DJ-1 was described in vitro to have glyoxalase activity, thereby detoxifying the MG metabolite, or deglycase activity, thereby removing the adduct formed by MG on proteins. Since Drosophila is an established model system to study signaling, neurodegeneration, and metabolic regulation in vivo, we asked whether DJ-1 contributes to MG detoxification in vivo. Using both DJ-1 knockdown in Drosophila cells in culture, and DJ-1β knock-out flies, we could detect no contribution of DJ-1 to survival to MG challenge or to accumulation of MG protein adducts. Furthermore, we provide data suggesting that the previously reported deglycation activity of DJ-1 can be ascribed to a TRIS buffer artifact.